2015
DOI: 10.1038/srep09378
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of expression of genes involved in glycosaminoglycan metabolism and lysosome biogenesis by flavonoids

Abstract: Flavonoids were found previously to modulate efficiency of synthesis of glycosaminoglycans (GAGs), compounds which are accumulated in cells of patients suffering from mucopolysaccharidoses (MPSs). The aim of this work was to determine effects of different flavonoids (genistein, kaempferol, daidzein) used alone or in combinations, on expression of genes coding for proteins involved in GAG metabolism. Analyses with DNA microarray, followed by real-time qRT-PCR revealed that genistein, kaempferol and combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…MPS are caused by the absence or malfunction of lysosomal enzymes needed to break down HS, CS, DS, KS, or HA GAGs [15] that leads to GAG accumulation in lysosomes in virtually all cells of the affected organism. It causes a progressive damage of tissues leading to severe dysfunctions of various organs, including the heart, bones, respiratory system, joints, and central nervous system (CNS), with an average expected lifespan of one or two decades [13,14,[16][17][18][19]. Depending on the lacking or deficient enzyme associated with the accumulated GAGs, 11 types and subtypes of MPS have been recognized [13,16,[18][19][20][21][22][23].…”
Section: Genistein Enhances or Reduces Glycosaminoglycan Quantity In mentioning
confidence: 99%
See 2 more Smart Citations
“…MPS are caused by the absence or malfunction of lysosomal enzymes needed to break down HS, CS, DS, KS, or HA GAGs [15] that leads to GAG accumulation in lysosomes in virtually all cells of the affected organism. It causes a progressive damage of tissues leading to severe dysfunctions of various organs, including the heart, bones, respiratory system, joints, and central nervous system (CNS), with an average expected lifespan of one or two decades [13,14,[16][17][18][19]. Depending on the lacking or deficient enzyme associated with the accumulated GAGs, 11 types and subtypes of MPS have been recognized [13,16,[18][19][20][21][22][23].…”
Section: Genistein Enhances or Reduces Glycosaminoglycan Quantity In mentioning
confidence: 99%
“…It causes a progressive damage of tissues leading to severe dysfunctions of various organs, including the heart, bones, respiratory system, joints, and central nervous system (CNS), with an average expected lifespan of one or two decades [13,14,[16][17][18][19]. Depending on the lacking or deficient enzyme associated with the accumulated GAGs, 11 types and subtypes of MPS have been recognized [13,16,[18][19][20][21][22][23]. Apart from MPS II, which is an X chromosome-linked disease, all other MPS types are inherited in an autosomal recessive manner [13,16,[21][22][23][24].…”
Section: Genistein Enhances or Reduces Glycosaminoglycan Quantity In mentioning
confidence: 99%
See 1 more Smart Citation
“…Already known biochemical actions of genistein include interactions with estrogen receptors (Martin et al 1978;Wang et al 1996), inhibition of tyrosine kinase activities (Akiyama et al 1987;Moskot et al 2014;Moskot et al 2015), and inhibition of topoisomerase II function (Markovits et al 1989;Salti et al 2000). However, these activities cannot explain the mechanism of either genistein-mediated alleviation of homocysteininduced changes in cell cultures or genisteindependent decrease in plasma homocysteine levels in patients.…”
Section: Aq2mentioning
confidence: 99%
“…This inhibition appears to be due to impairment of the epidermal growth factor receptor activity, and further down-regulation of the signal transduction, which normally leads to stimulation of expression of genes coding for enzymes involved in GAG synthesis [5]. Despite different laboratories reported various effects of genistein on GAG production and accumulation in different cell lines [4][5][6][7][8][9], very recent studies, employing microarray analyses followed by real-time quantitative RT-PCR identified particular genes coding for enzymes necessary for GAG synthesis which were inhibited by genistein, while most of genes for GAG lysosomal hydrolases were stimulated by this isoflavone [10,11]. This stimulation was apparently due to positive regulation of the transcription factor EB (TFEB), a master regulator for lysosomal biogenesis and function [11].…”
Section: Accepted Manuscriptmentioning
confidence: 99%